1997
DOI: 10.1002/bjs.1800840416
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance and mood after a weekend on call in a surgical unit

Abstract: A weekend on call has significant deleterious effects on cognitive performance and mood. The findings have implications for staffing levels and the design of duty rosters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 3 publications
0
22
1
1
Order By: Relevance
“…This conventional analysis is largely in accordance with some previous RT findings. 8 However, both simple and more complex RT tasks were significantly affected by sleep loss in our study contrasting with the findings of Orton and Gruzelier, 7 possibly due to the differences in the length of the tests used.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This conventional analysis is largely in accordance with some previous RT findings. 8 However, both simple and more complex RT tasks were significantly affected by sleep loss in our study contrasting with the findings of Orton and Gruzelier, 7 possibly due to the differences in the length of the tests used.…”
Section: Discussioncontrasting
confidence: 99%
“…An overall score of attention speed showed a significant deterioration following a weekend on-call. 8 Recently, a new yardstick has emerged to establish the importance of changes in performance, particularly those related to sleep deprivation. After 17 hours of sustained wakefulness, hand-eye coordination was reported to deteriorate to a level achieved by a blood alcohol concentration (BAC) of 0.05%.…”
mentioning
confidence: 99%
“…Most studies show that mood is lowered after a long on-call shift and young doctors report feeling more confused and less confident. 14 These psychological effects are mirrored where the quality of care is considered. Errors increase with sleep loss, and data on shift work show a rise in industrial injuries on the night shift.…”
Section: A Way Forwardmentioning
confidence: 99%
“…Other studies have reported that sleep-deprived residents demonstrated impaired alertness or concentration [7, 8], were less efficient, and made more clinical errors [9]. Some studies have reported that working acute night shifts reduced the performance of monotonous tasks and increased sleepiness [10].…”
Section: Introductionmentioning
confidence: 99%